Smart pond detector application in barramundi quality of water / Ahmad Nazirul Mohd, Ahmad Zakwan Ghazali and Fazreeq Faiz Anuar - Mohd, Ahmad Nazirul; Ghazali, Ahmad Zakwan; Anuar, Fazreeq Faiz (2015)
A pH (power of hydrogen) is a simply a measurement of the acidity or alkalinity of a solution. A pH of 7 is considered to be 'Neutral' neither acid or alkaline while pH above 7 is alkaline or 'Base' and below 7 is acidic. For final year project, Smart Pond Detector has been chosen as a project that wanted to be done. The reason of carried out this project because each source of water on earth has a different concentration of salt. So, this project will control the concentration of salt in pond at the house. The concentration of salt that needed by the aquatic living are different such as concentration at the river and at the sea are totally different. So, this thing can ease the people that want to farm different type of aquatic living that having type of habitat at the same time. When this project is done, it can be implemented at the house that have a pond. Lastly, this project want to be done because aquatic living also need to stay healthy where ever they live.